2020
DOI: 10.37290/ctnr2641-452x.19:21-28
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of the Metabolic Effects of Diet-Induced Obesity by Probiotic Lactobacillus Paracasei K56 and Prebiotic α-Galactooligosaccharides

Abstract: While both probiotics and prebiotics have an important role in controlling obesity, the effectiveness of probiotic bacteria is strain dependent. Herein, we have examined the role of Lactobacillus paracasei strain K56 and prebiotic α-galactooligosaccharides in modulating metabolic consequences of obesity. To this end, we have employed high fat diet induced obesity in a mouse model. The results show that mice fed a high fat diet exhibited increased body weight, adiposity, and abnormal glucose and lipid metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Some specific Lacticaseibacillus paracasei improved glycolipid metabolism [23,24]. Lacticaseibacillus paracasei K56 was isolated from the intestinal tract of children, improved obesity, and regulated the intestinal flora of the host with a high-fat diet [9,10]. However, the mechanism of action of K56 on lipid…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some specific Lacticaseibacillus paracasei improved glycolipid metabolism [23,24]. Lacticaseibacillus paracasei K56 was isolated from the intestinal tract of children, improved obesity, and regulated the intestinal flora of the host with a high-fat diet [9,10]. However, the mechanism of action of K56 on lipid…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognized as safe (GRAS) [8]. K56 has demonstrated the potential to prevent obesity, effectively improving glycolipid metabolism in mice fed with a high-fat diet [9,10]. However, probiotics do not directly interact with adipose tissues in vivo, and glycolipid metabolism is a complex process involving lipogenesis and lipolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In a previously reported animal study, high fat diet induced obese mice were treated by gavage five times a week with freshly prepared K56 (10 6 CFU/day or 10 8 CFU/day) alone or in combination with α- galactooligosaccharides for 12 weeks. After treatment, all probiotic groups significantly decreased body weight gain and visceral fat than high fat diet (HFD) group, especially at the dosage of 10 8 CUF/day alone or combined with α-GOS had lower body weight and fat gain than 10 6 CFU/day group [ 23 ]. In another animal study, HFD-fed mice were administered K56 suspension of 10 7 CFU/day, 10 9 CFU/day, and 10 11 CFU/day.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published animal study, a novel probiotic strain Lacticaseibacillus paracasei K56, isolated from the intestine of a healthy child, was treated by gavage at various doses to HFD-fed mice for 12 weeks. The results have shown that L. paracasei K56 significantly reduced body and fat mass and improved lipid metabolism [ 23 ]. In another animal study, administration of Lacticaseibacillus paracasei K56 effectively attenuated obesity parameters, such as body weight, insulin-resistance, plasma glucose and lipids; The beneficial effects may be related to the restored host gut microbiota [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with Lactobacillus paracasei K56 and α-galacto-oligosaccharides significantly reduced body weight and fat mass, especially when α-galacto-oligosaccharides were given with a high concentration of L. paracasei K56. In addition, both α-galacto-oligosaccharides and Lactobacillus paracasei K56 significantly modulated obesity and improved lipid metabolism (Min et al, 2020). After examining the prebiotic effects of Lactobacillus fermentum CECT5716 in high-fat diet-induced obese mice, this prebiotic was demonstrated to possess antiobesity and anti-inflammatory properties, improve endothelial dysfunction and intestinal dystrophy, restore the abundance of Akkermansia, reduce the proportions of Erysipelotrichi and Clostridium, and increase the abundance of Bacteroidetes.…”
Section: Research Status Of Lactic Acid Bacteria In the Prevention An...mentioning
confidence: 99%